Pengaruh Komunikasi Sosial Antar Budaya Terhadap Etika Karyawan Di Perseroan Terbatas Surya Madistrindo - Nyoman Rycko Dwicahya Ary Sanjaya (BICARA: Jurnal Ilmu Komunikasi, 2023)
Employee ethics at work have an influence on company performance because it is a system that supports the achievement of company targets and goals. Social communication and intercultural communication are some of the determining factors for employees in forming a work atmosphere that supports employee performance productivity, so researchers are interested in conducting research related to "The Influence of Social Communication and Intercultural Communication on Employee Ethics in the Limited Liability Company Surya Madistrindo Mataram Branch". This research was conducted using a quantitative scientific discipline with data obtained through a questionnaire which was distributed to 57 employees at the Mataram Branch Limited Liability Company (PT) Surya Madistrindo. The questionnaire was then processed with SPSS 20 through social, intercultural and ethical communication theory. In this study, it was found that social communication has a positive effect on employee ethics based on the results of the t-value of (3.261), while intercultural communication also has an effect on employee ethics with a t-value of (4.667). These results conclude that social communication and intercultural communication together have a positive influence on employee ethics at PT Surya Madistrindo Mataram Branch based on aspects of attitude and behavior, aspects of appearance, aspects of how to speak, aspects of gestures and aspects of how to ask questions.